Self-efficacy parenting and nursing stress: Study on mother from spectrum autism children - Iskayanti, Andini; Hartini, Nurul (Psikohumaniora: Jurnal Penelitian Psikologi, 2019)
This study aimed to examine parenting self-efficacy especially in mothers who have children with autism spectrum disorder and who suffer from parenting stress. They showed symptoms of anxiety and depression, which indicated parenting stress. Parenting self-efficacy is predicted to be a factor that can decrease anxiety and depression. There were 45 mothers from the city of Surabaya selected through purposive sampling technique to be the participants of this study. The data were collected through a survey using questionnaires concerning Self-efficacy for Parenting Task Index (SEPTI) and Parenting Stress Index Short Form (PSI-SF). The data analyzed using the statistical parametric of the Pearson product-moment correlation coefficient showed that the correlation coefficient was -0.424 and the significance was 0.004. It was concluded that high parenting self-efficacy of mothers who have children with autism spectrum disorder correlates with parenting stress.